CONSUMER ACCEPTANCE OF HIGH ZINK NUTRITIONAL RICE - Muhammad Sudirman Akilie; Ulfira Ashari; Deyvie Xyzquolyna (Agricultural Socio-Economics Journal, 2023)
Nutrizinc rice is a biofortified variety designed with the advantage of high specific nutritional value, especially at higher levels of zinc nutrition compared to Ciherang rice. The mineral zinc is useful for preventing stunting in humans, and to help protect the human immune system from the attack of the COVID-19 virus. However, this variety has just been promoted by The Assessment Institute for Agricultural Technology (AIAT, in Indonesian: Balai Pengkajian Teknologi Pertanian, BPTP) Gorontalo Province so people are still not familiar with this rice. Therefore, it is important to conduct research related to the analysis of the level of consumer acceptance aimed at knowing consumer preferences and attitudes towards the attributes of high-zinc nutritious rice. The study had 60 respondents who were chosen by chance (accidental). This study used Chi Square analysis (X2) to see the differences in consumer preferences for the attributes of high zinc nutritional rice with various cooking methods and the ratio between rice and water. Meanwhile, Fishbein Multi-attribute analysis was used to determine consumer attitudes towards the attributes of high-zinc nutritional rice. The results showed that the different methods of cooking and adding water to the rice did not significantly change the flavor, color, and aroma of the rice, on the contrary, it only changed the texture of the rice. The high-zinc nutritional rice that consumers like was rice that had a slightly sweet flavor, fluffier texture, bright white color, and has no odor. In addition, the color and texture attributes of rice with high zinc nutrition were the most dominant considerations compared to other attributes in deciding to buy or consume rice with high zinc nutrition.